The Interaction between KCNJ11 Gene Polymorphism and Refined Carbohydrates Intake on Obesity in Indonesian Adolescents - Huriyati, Emy; Luglio, Harry F.; Sadewa, Ahmad H.; Juffrie, Mohammad (Current Nutrition & Food Science, 2020)
Background: Obesity has been associated with genetic and environmental factors. Although carbohydrate intake was previously shown to be associated with a high risk of obesity and insulin resistance, some studies reported that genetic factors also have a role in this association. KCNJ11 is a gene involved in protein K-ATP channels of pancreatic beta cells and previously associated with obesity. Objective: The objective of this study was to determine the interaction between KCNJ11 polymorphism with a high intake of refined carbohydrates in relation to the incidence of obesity in adolescents. Methods: This was an observational study with a case-control design. The subjects of this study were male and female adolescents from 10 high schools in Yogyakarta. Dietary intake, body weight, and height were collected. KCNJ11 gene polymorphism was detected by polymerase Chain Reaction- Restriction Fragment Length Polymorphism (PCR-RFLP) method. Results: There is a significant association between KCNJ11 polymorphism with a high intake of refined carbohydrates in the incidence of obesity in adolescents (OR = 2.35, p =0.036). Conclusion: There is a significant association between the KCNJ11 polymorphism with a high intake of refined carbohydrates in adolescent obesity.
Keywords: obesity